Miracle of imaging: the truth is out there! - Hassan, Radhiana; Abd. Aziz, Azian; Mohd Yusof, Mubarak; Mohd Ralib, Ahmad Rashid; Sa'at@Yusof, Azlin; Che Mohamed, Siti Kamariah (2010)
Introduction In medical practice, we encounter many diseases, which can manifest in different ways. Most of the time, careful history taking and meticulous clinical examination can easily direct the clinician towards an accurate diagnosis. While with others, they may need further supporting evidence either from laboratory investigations or imaging. Likewise, the radiologists face daily challenges of analyzing and interpreting high volume of images in a timely manner. Appropriate diagnosis or differential diagnosis can be derived from cases with good clinical correlation. However, it can be misleading for the radiologists when interpreting images in cases where the history or clinical presentation is unclear although meticulous image assessment for high quality diagnostic and patient care are indeed paramount.